Triphasic esterification of butanol and butyric acid in fermentation media. (February 2017) - Ng, Choong Hey; Yang, Kun-Lin
Graphical abstract: Highlights: Triphasic organic/aqueous/fluorous system is used as an esterification medium. The ester products form a distinct phase on top to facilitate recovery. Multiple cycles of esterification with product removal improve the yield by 50%. The system is used to produce butyl butyrate using spent culture media. Bacterial growth is unaffected when fermentation is done in triphasic system. Abstract: Butanol and butyric acid produced from acetone-butanol-ethanol (ABE) fermentation can be used to produce butyl butyrate, an important fragrance ester. However, low levels of butanol and butyric acid need to be purified from culture media first with energy-intensive distillation processes. In this study, a triphasic (organic/aqueous/fluorous) system is developed to esterify butanol and butyric acid in spent culture media into butyl butyrate directly without purification. The produced butyl butyrate forms a distinct organic phase floating on top and can then be separated easily. In a model system containing 37.1 g/L of butanol and 44.1 g/L of butyric acid, 57% of the butanol is converted to butyl butyrate after 8 h of esterification. With multiple cycles of esterification and product removal, butanol conversion can be further increased to 86%. When spent culture medium containing 7.12 g/L of butanol and 4.81 g/L of butyric acid is used for esterification, 38% of butanol (0.36 mmol) is consumed and 0.33 mmol of butyl butyrate is produced. However, when ABE fermentation and esterification are carried out simultaneously, only 0.042 mmol of butyl butyrate is produced, probably due to the incompatible pH requirements for cell growth (pH 5–7) and esterification (pH 2–3).